2019
DOI: 10.1186/s42466-019-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar nerve integrity predicts 1-year outcome in cervical spinal cord injury

Abstract: Background: Accurate predictors of neurological recovery after cervical spinal cord injury are needed. Particularly, to tailor adequate rehabilitation plans. However, objective and quantifiable predictors are sparse. Methods: Within the prospective European Multicenter Study about Spinal Cord Injury (EMSCI) registry, cervical spinal cord injury patients are monitored at fixed follow up visits (2, 4, 12, 24, and 48 weeks after injury) clinically and with ulnar nerve electroneurography. Associations of ulnar ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Neurophysiologic techniques, such as measuring nerve conduction, motor-evoked potential (MEP), and somatosensory-evoked potentials (SEP), provide objective measures of neuronal integrity and allow the differentiation between demyelination and axonal damage [98••, 99]. Their value as independent tool for stratifying SCI patients into sub-groups and their predictive utility were already demonstrated and validated several years ago [99][100][101][102]. However, some questioned whether these electrophysiological parameters could add valuable information for improving functional outcome prediction.…”
Section: Neurophysiologic Markersmentioning
confidence: 99%
“…Neurophysiologic techniques, such as measuring nerve conduction, motor-evoked potential (MEP), and somatosensory-evoked potentials (SEP), provide objective measures of neuronal integrity and allow the differentiation between demyelination and axonal damage [98••, 99]. Their value as independent tool for stratifying SCI patients into sub-groups and their predictive utility were already demonstrated and validated several years ago [99][100][101][102]. However, some questioned whether these electrophysiological parameters could add valuable information for improving functional outcome prediction.…”
Section: Neurophysiologic Markersmentioning
confidence: 99%
“…Hug et al 127 used the EMSCI database to determine the predictive utility of the ulnar CMAP. They showed that higher ulnar CMAP at 4 weeks was predictive of an improved AIS grade at 1 year after injury.…”
Section: Identifying Lmn Lesions For Nerve Transfer Surgerymentioning
confidence: 99%
“…In general, studies using the EMSCI database show that the ulnar CMAP appears to be associated clinical severity of SCI. 40,118,127,128 It is reasonable to suppose that the "motor completeness" in SCI is, in part, dependent on LMN health. 129 The evidence that LMN lesions likely play an important prognostic role is certain to continue to expand and existing studies likely already justify the implementation of routine electrodiagnostic evaluation of the upper extremities following SCI.…”
Section: Identifying Lmn Lesions For Nerve Transfer Surgerymentioning
confidence: 99%
See 2 more Smart Citations